2011
DOI: 10.1038/tp.2011.21
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational impact of intimate partner violence on methylation in the promoter of the glucocorticoid receptor

Abstract: Prenatal exposure to maternal stress can have lifelong implications for psychological function, such as behavioral problems and even the development of mental illness. Previous research suggests that this is due to transgenerational epigenetic programming of genes operating in the hypothalamic–pituitary–adrenal axis, such as the glucocorticoid receptor (GR). However, it is not known whether intrauterine exposure to maternal stress affects the epigenetic state of these genes beyond infancy. Here, we analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
311
2
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(338 citation statements)
references
References 36 publications
10
311
2
15
Order By: Relevance
“…Fourth, information on exposure to trauma prior to treatment was not available for this sample. Traumatic experiences in childhood have been demonstrated to have lasting effects on DNA methylation of both the FKBP5 and GR genes 11, 12, 14, 15, 16, 17. Therefore, we are unable to make any conclusions regarding other environmental factors that may have influenced baseline DNA methylation and subsequent changes in DNA methylation during active treatment.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Fourth, information on exposure to trauma prior to treatment was not available for this sample. Traumatic experiences in childhood have been demonstrated to have lasting effects on DNA methylation of both the FKBP5 and GR genes 11, 12, 14, 15, 16, 17. Therefore, we are unable to make any conclusions regarding other environmental factors that may have influenced baseline DNA methylation and subsequent changes in DNA methylation during active treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Studies of early experiences in rats found that DNA methylation of the GR promoter region was altered by maternal care, which in turn was associated with GR expression and HPA responses to stress 12. In humans, stressful life events (e.g., trauma and abuse) have been associated with higher DNA methylation at the GR promoter region13, 14, 15, 16, 17, 18 as well as differential GR expression and biological markers of HPA‐axis activity, such as salivary cortisol 13, 14. Furthermore, GR methylation has been implicated in the development of PTSD following trauma 19.…”
Section: Introductionmentioning
confidence: 99%
“…A positive association was observed between methylation status of the NR3C1 promoter in offspring at 10-19 years of age and maternal exposure to intimate partner violence (IPV) during pregnancy (Radtke et al, 2011). A positive correlation was also found between maternal prenatal stress associated with living in the Democratic Republic of Congo, a region plagued by ongoing war and violence, and newborn methylation in the promoter of NR3C1 in umbilical cord blood (Mulligan et al, 2012).…”
Section: Epigeneticsmentioning
confidence: 90%
“…Precisely, the NR3C1 locus was found to be hypermethylated in children whose mothers suffered from depression and anxiety during the third trimester of their pregnancy (51). Women's experience of intimate partner violence during pregnancy also has been associated with increased NR3C1 methylation in their adolescent offspring (52). When women were exposed to the Tutsi genocide during pregnancy, their children had higher methylation of the NR3C1 exon 1F than offspring from nonexposed women (53).…”
Section: Discussionmentioning
confidence: 99%